Structural and functional alterations in the retrosplenial cortex following neuropathic pain - Barrière, David André (2019)
Human and animal imaging studies demonstrated that chronic pain profoundly alters the structure and the functionality of several brain regions. In this article, we conducted a longitudinal and multimodal study to assess how chronic pain affects the brain. Using the spared nerve injury model which promotes both long-lasting mechanical and thermal allodynia/hyperalgesia but also pain-associated comorbidities, we showed that neuropathic pain deeply modified the intrinsic organization of the brain functional network 1 and 2 months after injury. We found that both functional metrics and connectivity of the part A of the retrosplenial granular cortex (RSgA) were significantly correlated with the development of neuropathic pain behaviours. In addition, we found that the functional RSgA connectivity to the subiculum and the prelimbic system are significantly increased in spared nerve injury animals and correlated with peripheral pain thresholds. These brain regions were previously linked to the development of comorbidities associated with neuropathic pain. Using a voxel-based morphometry approach, we showed that neuropathic pain induced a significant increase of the gray matter concentration within the RSgA, associated with a significant activation of both astrocytes and microglial cells. Together, functional and morphological imaging metrics of the RSgA could be used as a predictive biomarker of neuropathic pain.